2018
DOI: 10.1177/2047487318815320
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to air pollution raises circulating levels of proprotein convertase subtilisin/kexin type 9 in obese individuals

Abstract: Aims Exposure to airborne particulate matter has been consistently associated with early death and increased morbidity, particularly raising the risk of cardiovascular disease. Obesity, one of the leading cardiovascular disease risk factors, increases susceptibility to the adverse effects of particulate matter exposure. Proprotein convertase subtilisin/kexin type 9 has been related to a large number of cardiovascular risk factors, e.g. atherogenic lipoproteins, arterial stiffness and platelet activation. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…In the context of an optimal treatment strategy aimed at reducing CV risk, it is useful to identify effects that are specific or shared by either lipid lowering drugs, or anti-inflammatory drugs or a combination of both [139,144]. Moreover, since association studies do not necessarily imply a causal role of PCSK9 in the inflammatory response [145] and data from carriers of loss-of-function mutations in PCSK9, aimed to establish a correlation between plasma inflammation markers and PCSK9 levels are scanty and not conclusive [146,147], evidence Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of an optimal treatment strategy aimed at reducing CV risk, it is useful to identify effects that are specific or shared by either lipid lowering drugs, or anti-inflammatory drugs or a combination of both [139,144]. Moreover, since association studies do not necessarily imply a causal role of PCSK9 in the inflammatory response [145] and data from carriers of loss-of-function mutations in PCSK9, aimed to establish a correlation between plasma inflammation markers and PCSK9 levels are scanty and not conclusive [146,147], evidence Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the relationship between PCSK9 and CV risk, although some studies on PCSK9 levels did not report any association with CV events [38,39], other population studies, meta-analyses and genome-wide association studies have supported the predictivity of PCSK9 levels in CV events [40][41][42]. A genetic reduction of PCSK9 levels by 50% is associated with a similar percent reduction of coronary heart disease (CHD) risk [43] and a genetic large-scale study on 337,536 individuals of British ancestry reported that the rs11591147 loss-of-function PCSK9 mutation had a protective effect not only on hyperlipidemia but also on the risk of CHD (-27%) and ischemic stroke (-39%) [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is important to note that Macchi and colleagues investigated PM 10 as a measure of air pollution only. 9 This partly limits the conclusion of study results regarding the exposure of lower degrees of PM (e.g. PM 2.5 ) and the different compositions of constituents (e.g.…”
mentioning
confidence: 93%
“…Further adjustment for potential confounders revealed that this association was limited to obese individuals with lower levels of interferon-g. For short-term exposure to PM 10 , no significant associations were found. 9 PCSK9 binds to the receptor for low-density lipoprotein (LDL) particles and thereby initiates the internalisation of both LDL particles and the LDL receptor into the liver cells. Therapeutically, the blockade of PCSK9 with specific antibodies is paving new avenues in the management of dyslipidemia.…”
mentioning
confidence: 99%